IL-6 secretion in osteoarthritis patients is mediated by chondrocyte-synovial fibroblast cross-talk and is enhanced by obesity - Mark J. Pearson (Nature Portfolio, 2017)
Abstract Increasing evidence suggests that inflammation plays a central role in driving joint pathology in certain patients with osteoarthritis (OA). Since many patients with OA are obese and increased adiposity is associated with chronic inflammation, we investigated whether obese patients with hip OA exhibited differential pro-inflammatory cytokine signalling and peripheral and local lymphocyte populations, compared to normal weight hip OA patients. No differences in either peripheral blood or local lymphocyte populations were found between obese and normal-weight hip OA patients. However, synovial fibroblasts from obese OA patients were found to secrete greater amounts of the pro-inflammatory cytokine IL-6, compared to those from normal-weight patients (p < 0.05), which reflected the greater levels of IL-6 detected in the synovial fluid of the obese OA patients. Investigation into the inflammatory mechanism demonstrated that IL-6 secretion from synovial fibroblasts was induced by chondrocyte-derived IL-6. Furthermore, this IL-6 inflammatory response, mediated by chondrocyte-synovial fibroblast cross-talk, was enhanced by the obesity-related adipokine leptin. This study suggests that obesity enhances the cross-talk between chondrocytes and synovial fibroblasts via raised levels of the pro-inflammatory adipokine leptin, leading to greater production of IL-6 in OA patients.